Kadar TNF-, IL-6 dan Trofoblas pada Preeklampsia-Eklampsia - Indrato Adi Susian; Suharsono Suharsono; S Hadijono (MEDIA MEDIKA INDONESIANA, 2009)
The level of TNF-, IL-6 and trophoblast in preeclampsia-eclampsiaBackground: Pre eclampsia–eclampsia (PE-E) is the highest cause of maternal death. Up to the present time, PE-E is still the disease of theories, where the patofisiology is still unclear. Invitro research reported that increase of TNF–α and IL–6 in PE-E will cause the placenta hypoxia. This condition will trigger the secretion of pro inflammatory cytokine from fetoplacenta which will cause the rejection in trophoblast invasion. The purpose of this study was to analyze the association between the TNF–α and IL–6 rate/expression with infarct and placental tissue apoptosis.Methods: The study was done during the period of July 2005–October 2005. The subjects were 17 parturient non PE-E and 18 parturient PE-E who delivered at Dr. Kariadi Hospital Semarang. The TNF–α and IL–6 rate/expression were measured from the blood sample and placental tissue with ELISA method and imunohystochemical by acidine orange painting. The difference of TNF–α and IL–6 rate/expression with the size of infarct and apoptosis were tested by Mann-Whitney test and the correlation with Spearman test.Results: The mean size of infarct in normal subjects was 12.5% compared to PE-E which was 35.3% (p=0.001). The percentage of apoptosis in normal and PE-E subjects were 32.3% and 71.0% respectively (p=0.001). The mean rate of TNF–α of placenta and blood serum in normal and PE-E subjects were 1.7 pg/mL, 2.0 pg/mL, 2.3 pg/mL and 2.8 pg/mL respectively (P1 and P2 <0.001). The mean placenta and blood serum IL-6 in normal and PE-E subjects were 0.6 pg/mL, 1.3 pg/mL, 1.4 pg/mL, and 2.0 pg/mLrespectively showing significant difference between the two groups. There were strong associations between placenta and serum TNF–α and IL–6 with the size of infarct and percentage of placenta apoptosis.Conclusions: The level of pro inflammatory cytokine in serum as well as in placenta of subjects with PE-E is higher than those without PE-E and there is strong correlation between pro inflammatory cytokine expression in serum and placenta with the size of infarct and placental apoptosis.Keywords: TNF-α, IL-6, infarct, apoptosis, placenta, preeclampsia, eclampsia.ABSTRAKLatar Belakang: Preeklampsia-Eklampsia (PE-E) merupakan penyebab kematian maternal paling tinggi. Sampai saat ini PE-E masih merupakan the disease of theories, dengan patofisiologi yang masih belum diketahui dengan jelas. Pada penelitian invitro dilaporkan peningkatan kadar TNF-α dan IL-6 dapat menimbulkan hipoksia plasenta. Hal tersebut dapat memicu sekresi sitokin proinflamasi dari fetoplasenta yang akan menyebabkan penolakan invasi trofoblas. Tujuan penelitian ini adalah untuk mengetahui hubungan antara kadar/ekspresi TNF-α dan IL-6 dengan infark dan apoptosis jaringan plasenta.Metode: Penelitian dilaksanakan pada periode Juli 2005–Oktober 2005. Subjek penelitian adalah 17 parturient non PE-E dan 18 parturient PE-E yang melahirkan di RSUP Dr. Kariadi Semarang. Kadar/ekspresi TNF-α dan IL-6 diukur dari sampel darah vena dan jaringan plasenta dengan metode ELISA dan imunohistokimia (Quantikine, USA). Luas infark plasenta diukur secara makroskopik, apoptosis diukur secara imunohistokimia dengan pengecatan acridine orange. Perbedaan kadar/ekspresi TNF-α, IL-6, luas infark dan persentase apoptosis antara subjek normal dengan PE-E diuji dengan uji Mann-Whitney. Korelasi antara TNF-α dan IL-6 dengan luas infark dan apoptosis diuji dengan uji korelasi Spearman.Hasil: Rerata luas infark subjek normal adalah 12.5%, sedangkan pada PE-E adalah 35.3% (p=0.001). Persentase apoptosis subjek non PE-E dan PE-E adalah 32.3%, dan 71.0% (p=0.001). Rerata kadar TNF-α plasenta subjek non PE-E dan PE-E adalah 1.7 pg/mL, dan 2.0 pg/mL (p<0.001). Rerata kadar TNF-α serum subjek non PE-E dan PE-E adalah 2.3 pg/mL, dan 2.8 pg/mL (p<0.001). Rerata kadar IL-6 plasenta subjek normal adalah 0.6 pg/mL, pada PE-E adalah 1.3 pg/mL (p<0.001). Rerata kadar IL-6 serum subjek non PE-E dan PE-E adalah 1.4 pg/mL, dan 2.0 pg/mL (p<0.001). Dijumpai korelasi kuat antara TNF-α, IL-6 serum dan plasenta dengan luas infark dan persentase apoptosis plasenta  (p<0.001).Simpulan: Kadar sitokin proinflamasi pada serum maupun plasenta parturient PE-E lebih tinggi dibanding non PE-E. Ada hubungan antara kadar/ekspresi sitokin proinflamasi pada serum dan plasenta dengan luas infark dan apoptosis jaringan plasenta